2015
DOI: 10.1007/s11581-015-1402-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and performance of cobalt-free perovskite-type La0.6Ba0.4Fe0.8Ni0.2O3 − δ cathode material for intermediate-temperature solid oxide fuel cells

Abstract: A novel cobalt-free perovskite La 0.6 Ba 0.4 Fe 0.8 Ni 0.2 O 3 − δ (LBFN) powder was synthesized using a combustion method. The phase composition, electrical conductivity, thermal expansion coefficient (TEC), and electrochemical properties of LBFN were systematically investigated. The X-ray diffraction (XRD) results revealed that LBFN had a high chemical compatibility with Ce 0.8 Sm 0.2 O 2 − δ (SDC). The LBFN cathode exhibited a competitive electrode area-specific resistance (ASR) for the symmetric cell based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It can be concluded that Pr 0.5 Ba 0.5 Fe 1-x Ni x O 3-δ (x = 0 and 0.2) oxides have the potential to be cathode materials for SOFCs. Moreover, all of them have relatively excellent electrochemical performance when Ni doping amount is 0.2 in the A-site alkaline earth metal-doped cobalt and strontium-free cathode materials, as reported in La 0.6 Ba 0.4 Fe 0.8 Ni 0.2 O 3-δ [28], La 0.6 Ca 0.4 Fe 0.8 Ni 0.2 O 3-δ [29], Pr 0.4 Ca 0.6 Fe 0.8 Ni 0.2 O 3 [30], and Pr 0.5 Ba 0.3 Ca 0.2 Fe 1-x Ni x O 3-δ [31]. Motivated by these findings, we prepared novel perovskite Pr 0.5 Ba 0.5 Fe 1-x Ni x O 3-δ (x = 0 and 0.2) as cathode electrocatalysts by a sol-gel method, study in detail its potential as a new type of perovskite cathode, and discuss the influence of Ni substitution on the structure and electrochemical properties of Pr 0.5 Ba 0.5 FeO 3-δ .…”
Section: Introductionmentioning
confidence: 77%
“…It can be concluded that Pr 0.5 Ba 0.5 Fe 1-x Ni x O 3-δ (x = 0 and 0.2) oxides have the potential to be cathode materials for SOFCs. Moreover, all of them have relatively excellent electrochemical performance when Ni doping amount is 0.2 in the A-site alkaline earth metal-doped cobalt and strontium-free cathode materials, as reported in La 0.6 Ba 0.4 Fe 0.8 Ni 0.2 O 3-δ [28], La 0.6 Ca 0.4 Fe 0.8 Ni 0.2 O 3-δ [29], Pr 0.4 Ca 0.6 Fe 0.8 Ni 0.2 O 3 [30], and Pr 0.5 Ba 0.3 Ca 0.2 Fe 1-x Ni x O 3-δ [31]. Motivated by these findings, we prepared novel perovskite Pr 0.5 Ba 0.5 Fe 1-x Ni x O 3-δ (x = 0 and 0.2) as cathode electrocatalysts by a sol-gel method, study in detail its potential as a new type of perovskite cathode, and discuss the influence of Ni substitution on the structure and electrochemical properties of Pr 0.5 Ba 0.5 FeO 3-δ .…”
Section: Introductionmentioning
confidence: 77%
“…Cobalt-free cathodes for intermediate temperature solid oxide fuel cells (IT-SOFCs) have been the subject of a number of studies in recent years. 1,2 In addition to avoiding shortcomings suffered by cobaltcontaining cathodes, such as high cobalt cost, low long-term chemical stability and high thermal expansion coefficient (TEC), some cobalt-free cathodes show comparable or even better electronic conductivity and catalytic activity for oxygen reduction reactions (ORR) comparing with those cobalt counterparts. 3 Among the cobalt-free cathodes, copper-iron based perovskite oxides have attracted much attention for their low price and abundance of copper, excellent electro-catalytic activity for ORR as well as favorable thermal and chemical stability to withstand the cathode environment.…”
mentioning
confidence: 99%